Is it time to reboot welfare economics? Overview - Coyle, D; Fabian, M; Beinhocker, E; Besley, T; Stevens, M (Wiley, 2023)
The contributions of economists have long included both positive explanations of how economic systems work and normative recommendations for how they could and should work better. In recent decades, economics has taken a strong empirical turn as well as having a greater appreciation of the importance of the complexities of real-world human behaviour, institutions, the strengths and failures of markets, and interlinkages with other systems, including politics, technology, culture and the environment. This shift has also brought greater relevance and pragmatism to normative economics. While this shift towards evidence and pragmatism has been welcome, it does not in itself answer the core question of what exactly constitutes ‘better’, and for whom, and how to manage inevitable conflicts and trade-offs in society. These have long been the core concerns of welfare economics. Yet, in the 1980s and 1990s, debates on welfare economics seemed to have become marginalised. The articles in this Fiscal Studies symposium engage with the question of how to revive normative questions as a central issue in economic scholarship.